2004
DOI: 10.1111/j.1365-2230.2004.01628.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-detected cutaneous melanomas in Italian patients

Abstract: Self-detection of suspicious pigmented skin lesion combined with rapid referral to dermatologic centres is the key strategy in the fight against melanoma. The investigation of factors associated with pattern of detection of melanoma (self- vs. nonself-detection) may be useful to refine educational strategies for the future. We investigated the frequency of melanoma self-detection in a Mediterranean population at intermediate melanoma risk. A multicentric survey identified 816 consecutive cases of cutaneous mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 9 publications
(9 reference statements)
4
59
2
5
Order By: Relevance
“…Poorer survival among men compared to women could be due to late stages of melanoma at the time of diagnosis. Women more often perform self-examination or tend to contact dermatologists for screening than men (13). It is reported that melanoma is rare before puberty, it tends to be more invasive during pregnancy, and decreases during post-menopausal years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poorer survival among men compared to women could be due to late stages of melanoma at the time of diagnosis. Women more often perform self-examination or tend to contact dermatologists for screening than men (13). It is reported that melanoma is rare before puberty, it tends to be more invasive during pregnancy, and decreases during post-menopausal years.…”
Section: Discussionmentioning
confidence: 99%
“…Since elderly people often have one or more chronic diseases (heart diseases, diabetes, and others) beside melanoma, they have weakened immune systems and lower survival rates of melanoma. Additionally, elderly people rarely perform self-examination or visit dermatologists for screening (13). As a consequence, melanoma is diagnosed at a late stage and greater depth, which impacts the prognosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Promotion of surveillance of skin pigmented lesions started in the 1980s and 1990s, and became popular mainly among young women. [20][21][22][23][24] It is commonly believed that ocular melanoma could also be associated with sun exposure, and thus, ocular melanoma patients and their doctors might have devoted greater attention to surveillance of skin pigmented lesions than other people. As a consequence, risk of subsequent cutaneous melanoma among ocular melanoma patients displayed epidemiological patterns similar to those observed for early detection of cutaneous melanoma in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial knowledge gaps were previously reported in studies on Italian melanoma patients [21], on persons at higher risk for developing melanoma in the UK [22] and also on transplant recipients [23]. A survey on awareness and knowledge about NMSC conducted on the general population in 7 countries [5] showed that 42% of Italians rarely or never applied a sunscreen when outside, with only Spain (47%) and the USA (49%) reporting a more frequent lack of sunscreen use.…”
Section: Discussionmentioning
confidence: 99%